Inertial sensor technologie for biomechanical recording in cross-country skiing - Rapp, W.; Stöggl, T.; Schiebel, F.; Lindinger, S. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Analysis of biomechanical Parameters in cross-country (XC) skiing is a challenging task to improve performance (Andersson et al 2010). Methods for movement analysis are often limited to laboratory situations, have limited time capacities and are expensive and therefore not available in routine training. Especially in young athletes, systems which can allocate relevant Information in short time under functional conditions would give an improvement in training. Therefore our goal was to adapt a system based on inertial sensors and already tested in gait analysis for the use in XC skiing training with a special focus on the integration of pole force measurements.